Chapter Valorization of Microalgae and Energy Resources - Jawiarczyk, Natalia (InTechOpen, 2020)
Microalgae biotechnology has grown very rapidly in the last few decades due to the multiple applications that these microorganisms have from pharmaceuticals and cosmetics to foods/feeds and biofuels. One of the main challenges in expanding this industry is to enlarge the single use of the biomass produced in addition to reducing the high biomass production cost of the current technologies. To overcome this bottleneck, the development of microalgae-based biorefineries has been proposed. The issue is to obtain as many bioproducts as possible from the cultivated biomass, including biofuels. Consequently, biodiesel production (from the lipid fraction), bioethanol (from carbohydrate fraction), and biogas or bio-oil (from the whole biomass) have been posited. In this book chapter, we review the current state of the art in the production of sustainable biofuels from microalgae and analyze the potential of microalgae to contribute to the biofuel sector.